Evaluating supply chain sustainability and agility using fuzzy logic approach: A case in Indonesian agroindustry - Hasibuan Sawarni; Yunita Ika; Zulkarnaen Iskandar (BIO Web of Conferences)
Agility and sustainability are critical, complementary concepts that enable businesses to navigate increasing uncertainties and complexities, as highlighted by the COVID-19 pandemic. In agroindustry, business processes face significant challenges in adapting to such unpredictable conditions, requiring robust strategies to enhance agility and sustainability. This study adopts a fuzzy logic approach to address ambiguities and uncertainties inherent in traditional performance assessments. A sustainability-agility evaluation framework was developed for the chicken meat industry, calculating FSCSAI values of 0.58, 0.72, and 0.86, which classify the industry as “very sustainable and agile (VSA)” based on Euclidean distance calculations. Additionally, challenges such as “using agile enabling technology” and “market response and sense” were identified, and actionable recommendations were proposed. This study makes two significant contributions: (1) demonstrating the applicability of the fuzzy logic method for assessing sustainability-agility in agroindustry and (2) providing insights for companies and policymakers to address critical challenges and implement targeted improvements. Despite its contributions, the study acknowledges limitations related to the reliance on decision-maker perceptions and emphasizes the importance of expert involvement. The findings offer a systematic framework for evaluating sustainability-agility indices, with practical applications for the chicken meat sector and beyond.